2015
DOI: 10.1371/journal.pone.0130807
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Cardiovascular Events in Treated Periodontitis: A Population-Based Follow-Up Study from Taiwan

Abstract: BackgroundThe aim of the present study was to identify the long-term major adverse cardiovascular events (MACE) in treated periodontitis patients in Taiwan.MethodsFrom the National Health Insurance Research Database (2001-2010), adult patients (≥ 18 years) with treated periodontitis were identified. Comparison was made between patients with mild form and severe form of treated periodontitis after propensity score matching. The primary end point was the incidence of MACE.ResultsA total of 32,504 adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 63 publications
2
32
0
1
Order By: Relevance
“…Most of the studies that exclude for the meta-analysis in this study also supported a positive association between PD and MI. A population-based study showed periodontitis was associated with an increased risk of major adverse cardiac events including MI occurrence [ 48 ]. Other studies also indicated that PD may be associated with MI in Turkish and Iran population [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies that exclude for the meta-analysis in this study also supported a positive association between PD and MI. A population-based study showed periodontitis was associated with an increased risk of major adverse cardiac events including MI occurrence [ 48 ]. Other studies also indicated that PD may be associated with MI in Turkish and Iran population [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…To select study data, 98,611 patients were identified, aged ≥18 years and who had received a first diagnosis of periodontitis (International Classification of Diseases, ninth edition, clinical modification [ICD‐9‐CM] code 523.4) in an ambulatory care visit (including outpatient departments of hospitals and clinics) from January 1, 2003 to December 31, 2012. According to previous studies, 17 , 18 a diagnosis of periodontitis was defined on the basis of the following procedures: 1) subgingival curettage, 2) periodontal flap operation, and 3) gingivectomy (excluding those with restorative or esthetic indications), as prescribed by the NHI system. Claim codes for these procedures were 91006C, 91007C, 91008C, 91009B, 91010B, 91011C, and 91012 under the NHI system.…”
Section: Methodsmentioning
confidence: 99%
“…Increased risk among patients with periodontitis of cardiovascular disease, pneumonia, dementia, Alzheimer's disease progression, osteoporosis, periprosthetic infection and gastric infection have been previously reported. In addition, periodontitis has also been reported to affect several liver diseases, such as hepatocellular carcinoma, cirrhosis, non‐alcoholic fatty liver disease and even liver transplantation .…”
Section: Discussionmentioning
confidence: 93%